A Polynomial with Galois GroupSL2(11) - Klüners, Jürgen (Journal of Symbolic Computation)
We compute a polynomial with Galois group SL₂(11) over ℚ. Furthermore we prove that SL₂(11) is the Galois group of a regular extension of ℚ (t).
Keywords: Computational Mathematics; Algebra and Number Theory